2021
DOI: 10.3389/fvets.2021.687071
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Lactic Acid Bacteria Strains of Potential Use as Feed Additives - The Basic Safety and Usefulness Criterion

Abstract: The spread of resistance to antibiotics is a major health concern worldwide due to the increasing rate of isolation of multidrug resistant pathogens hampering the treatment of infections. The food chain has been recognized as one of the key routes of antibiotic resistant bacteria transmission between animals and humans. Considering that lactic acid bacteria (LAB) could act as a reservoir of transferable antibiotic resistance genes, LAB strains intended to be used as feed additives should be monitored for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 74 publications
(170 reference statements)
3
33
0
Order By: Relevance
“…The MIC for kanamycin (128 mg/L) was 2-fold higher than the cut-off value specified by the EFSA (Table 2). This result was consistent with those of previous studies [55][56][57]. Many Lactobacillus species are resistant to aminoglycoside antibiotics, such as streptomycin, kanamycin, and gentamicin [58].…”
Section: Antimicrobial Resistance and Associated Genessupporting
confidence: 93%
See 1 more Smart Citation
“…The MIC for kanamycin (128 mg/L) was 2-fold higher than the cut-off value specified by the EFSA (Table 2). This result was consistent with those of previous studies [55][56][57]. Many Lactobacillus species are resistant to aminoglycoside antibiotics, such as streptomycin, kanamycin, and gentamicin [58].…”
Section: Antimicrobial Resistance and Associated Genessupporting
confidence: 93%
“…Many Lactobacillus species are resistant to aminoglycoside antibiotics, such as streptomycin, kanamycin, and gentamicin [58]. In addition, the enzyme aminoglycoside phosphotransferase type III, encoded by the aph(3 )-III gene, which is associated with resistance to kanamycin, has previously been detected in kanamycin-resistant L. plantarum strains [55,57]. Moreover, Feng et al [59] demonstrated that non-synonymous mutations in genes regulating major facilitator family protein, ABC transporter substrate-binding protein, and histidine kinase play an important role in increasing kanamycin resistance in L. plantarum.…”
Section: Antimicrobial Resistance and Associated Genesmentioning
confidence: 99%
“…These findings suggest that the food chain of animal products has been one of the important sources of ARB and ARGs transmission between animals and humans, posing a serious global public health threat. The abundant presence of ARB and ARGs transferring from animals to humans may have profound influences on future treatment, highlighting the importance of implementing hygiene measures to decrease the spread risk, thus, it urgently needs to be integrated, multi-sectoral, and global strategies ( Overdevest et al, 2011 ; Stefanska et al, 2021 ).…”
Section: Potential Risks Of Antibiotic Resistance In Food Animal Farmsmentioning
confidence: 99%
“…The latter is very useful as it may indicate presence of antibiotic resistance genes. Indeed, LAB are considered as a pool of transferable antibiotic resistance genes, the spread of which has been recognized as a major problem for public health [11,12]. Production of antimicrobial compounds is a useful trait that may assist in controlling of foodborne pathogens occurrence and proliferation.…”
Section: Introductionmentioning
confidence: 99%